Understanding traditional acupuncture a practical handbook for health practitioners in the Philippines - Pantig, Alphonse Vergara; Acupuncture Therapeutic and Research Center (Quezon City Acupuncture Therapeutic and Research Center and Socio-Pastoral Institute, 1996)
This book is intended to teach Filipinos traditional acupuncture within the context of primary health care in the Philippines. It uses the Chinese medical matrix. It also contains the theories of Yin and Yang and the five stages of change, the outline of the body in traditional Chinese medicine (TCM), basics of TCM physiology and pathophysiology and the four TM (traditional medicine) of diagnosis.
"It teaches traditional acupuncture within the context of primary health care in the Philippine setting; and the text explains the dynamics of acupuncture using the Chinese medical (TCM) matrix, rather than using the modern biomedical framework."
"This is the first book on traditional Chinese acupuncture published in the Philippines by Filipinos. It is a novel idea in the ATRC's decade-long teaching and clinical experience with the same healing modalities. Such experience has been crystallized into the teaching manual, entitled The Fundamental Theories of Traditional Chinese Medicine I (Version 1993-1). This manual has, in turn been one of the foundations of the Center's five-month traditional acupuncture training courses. It teaches traditional acupuncture within the context of primary health care in the Philippine setting; and the text explains the dynamics of acupuncture using the traditional Chinese medical (TCM) matrix rather than using the modern biomedical framework. This book is meant to be used with manuals or reading materials on points (acupoints) referred into the text."
Keywords: Acupuncture -- Handbooks, manuals, etc